2015
DOI: 10.1111/hpb.12463
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatectomy with vein reconstruction: technique matters

Abstract: Primary end-to-end and TV have superior patency than the alternatives after PV/SMV resection and should be the preferred techniques for short (<3 cm) reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 23 publications
(54 reference statements)
3
38
0
2
Order By: Relevance
“…This could explain why in our study the estimated patency rate of 52% at 12 months was inferior to that reported by others. 15,19,39,41 Fujii et al correlated the degree of stenosis with complications associated with anastomotic stenosis of the portal venous system, including refractory ascites, hepatic encephalopathy and gastrointestinal bleeding, and found that these complications only occurred in patients with stenosis 70%. 29 Furthermore, six out of 18 patients were reported to have complications without complete occlusion.…”
Section: Hpbmentioning
confidence: 99%
“…This could explain why in our study the estimated patency rate of 52% at 12 months was inferior to that reported by others. 15,19,39,41 Fujii et al correlated the degree of stenosis with complications associated with anastomotic stenosis of the portal venous system, including refractory ascites, hepatic encephalopathy and gastrointestinal bleeding, and found that these complications only occurred in patients with stenosis 70%. 29 Furthermore, six out of 18 patients were reported to have complications without complete occlusion.…”
Section: Hpbmentioning
confidence: 99%
“…Survival was correlated with the severity of venous involvement observed on preoperative CT scan (Nakao Types B, C, or D: median specific survival 26, 12, and 16 months, respectively). Post-operative chemotherapy had a positive impact on cancer-specific survival regardless of the type of venous extension (Nakao Type B: 26 vs. 13 months; Type C: 27 vs. 8.6 months, p < 0.0001; Type D: 20 vs. 9.6 months, p < 0.0052), but compliance to treatment at 3 and 6 months was lower in case of venous involvement (57 and 45% vs. 73 ; p = 0.0007) and blood transfusion (32 vs. 22%; p = 0.002) were significantly higher in the PD + VR group, but hospital mortality and survival were comparable (18 months in both groups) despite a higher R1 resection rate in PD+VR (63 vs. 52%; p = 0.003; 71% for histologically positive veins).…”
Section: Impact Of the Reconstruction Technique On The Long-term Permmentioning
confidence: 99%
“…On multivariate analysis, operative time (OR: 1.01; 95% CI, 1.01-1.02) and prosthetic graft (OR: 8.12; 95% CI, 1.1-74) were independent predictors of thrombosis (LE4). In another study including 90 VR with different techniques of reconstruction, the rate of thrombosis was 18% (16/90) and varied according to the technique (73). All reconstructions with primary end-to-end anastomosis (n = 28) or transverse venorrhaphy (n = 9) remained patent while longitudinal venorrhaphy (LV: n = 17), patch venoplasty (pv: n = 17) and graft reconstructions (GR: n = 19) were all associated with significant rates of thrombosis (p = 0.001 vs. no thrombosis).…”
Section: Impact Of the Reconstruction Technique On The Long-term Permmentioning
confidence: 99%
“…With current multidisciplinary management (neoadjuvant chemotherapy and radiation) these patients can benefit from en bloc vascular resection and this approach became standard of care in many high volume centers, where approximately 20-40% are treated by PD with en bloc venous resection and a 98% R0 rate is achieved (3,8).…”
Section: Discusionsmentioning
confidence: 99%